2012
DOI: 10.7201/earn.2012.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Estudio de la causalidad de los incendios forestales en Galicia

Abstract: Agradecimientos a: María Loureiro agradece la financiación recibida a través del programa ERANET-BIODIVERSA, proyecto "FIREMAN", número EUI2008-03685.Recibido en mayo de 2011. Aceptado en enero de 2012.REsumEn: El objetivo de este trabajo es estudiar la relevancia de los múltiples factores socio-económi-cos, agrarios y ambientales en la ocurrencia de los incendios forestales en Galicia. Los modelos econométri-cos presentados analizan el número de incendios ocurridos así como el número de hectáreas quemadas, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 9 publications
0
19
0
9
Order By: Relevance
“…These include social isolation of forest owners, lack of economic profitability of forests, abandonment of forests and agricultural lands, etc. (Barreal et al, 2012). In this particular study, seven policies were suggested as potential remedies to prevent or reduce the current magnitude and frequency of forest fires, as well as to improve the conservation status of forest and its profitability.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…These include social isolation of forest owners, lack of economic profitability of forests, abandonment of forests and agricultural lands, etc. (Barreal et al, 2012). In this particular study, seven policies were suggested as potential remedies to prevent or reduce the current magnitude and frequency of forest fires, as well as to improve the conservation status of forest and its profitability.…”
Section: Methodsmentioning
confidence: 98%
“…Between 1989 and, fires in the region represented 40% of the total burned area in Spain (some years even 60%), being mostly caused by human actions, whether negligent or intentional (Barreal et al, 2012). The alarming aging and dispersion of rural population, the decline of agriculture and the lack of appropriate silvicultural treatments are some of the main causes of the increase of forest fires in Galicia.…”
Section: Introductionmentioning
confidence: 98%
“…• Deficient land management: Galicia is one of the regions with the highest vegetal production and plant growth in Spain. Galician territories have been increasing their areas with highly According to specialized studies [30][31][32][33][34][35], forest fires in Galicia are directly related to a mixture of environmental-territorial plus social-economic factors. These factors can be considered well-known and predictable, but they typically exceed the capabilities of extinction means.…”
Section: Galicia Social Vulnerability and Wildfiresmentioning
confidence: 99%
“…Extensive livestock used to have an impact on the forest landscape, favoring the mosaics and reducing fuel in the mountains of Galicia [35]. The decline in extensive livestock farming that has taken place in Spain (around 30% between 2004-2015) is thus considered an aggravating factor of forest fires [40].…”
Section: Social and Economic Factorsmentioning
confidence: 99%
“…En España, la Comunidad Autónoma de Galicia ha sido la región que ha acaparado el mayor número de incendios forestales en lo que va de siglo XXI. Según los estudios especializados que se analizan posteriormente en este artículo (Barreal et al, 2011;Barreal et al, 2012;Balsa & Hermosilla, 2013;Loureiro & Barreal, 2015), los incendios forestales en esta comunidad autónoma están directamente relacionados tanto con factores socioeconómicos conexos a la vulnerabilidad social (el envejecimiento poblacional o la baja densidad de población unida al escaso desarrollo económico) como con factores naturales o medioambientales (la ganadería extensiva, las zonas abandonadas o las zonas de interfaz urbano forestal). Ello indudablemente refuerza la necesidad tanto de investigar la relación entre las variables socioeconómicas y los incendios forestales de esta región, como de encontrar qué variables son más determinantes en su producción.…”
unclassified